HIGH SERUM URIC ACID LEVELS AS A MARKER OF POOR CARDIOVASCULAR OUTCOME AND HIGH MORTALITY - Bano, Uzma; Gondal, Murtaza; Majeed, Dawar (Journal of Postgraduate Medical Institute, 2011)
Objective: To access the correlation of high serum uric acid with cardiovascular morbidity and mortality in patients having Congestive heart failure (CHF). Material and Methods: This descriptive cross sectional study was performed in Department of Medicine Fauji Foundation Hospital Rawalpindi. Serum uric acid was measured in 66 patients with CHF diagnosed on the basis of an ejection fraction < 50%. Patients were prospectively followed during a median followup period of 30 days with end points of cardiac death or rehospitalization. Out of 66 patients, 6 patients were lost to follow up at some stage of data collection and were excluded. Results: Out of 60 patients finally analyzed, 25 (41.7%) patients had normal uric acid and 35 (58.3%) patients had high uric acid. More patients with high uric acid levels were in severe heart failure as compared to those with normal uric acid levels (p= 0.00). Patients with high uric acid levels had more deaths (p= 0.484). Patients with higher uric acid levels required significantly more rehospitalization as compared to those with normal uric acid levels. Conclusion: High plasma uric acid level is a prognostic predictor in patients with CHF. Monitoring of uric acid may be useful for the management of patients with CHF.